2019
DOI: 10.20452/pamw.14981
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of long-term outcome in patients after percutaneous stent-assisted intervention on renal artery steno-occlusive atherosclerotic disease

Abstract: guidelines. 1,2 On the one hand, a series of observational studies indicated a significant decrease in blood pressure (BP) and / or creatinine levels. 3-7 Furthermore, a number of studies reported the effect of PTA for RAS on the reduction INTRODUCTION Stent-assisted percutaneous transluminal angioplasty (PTA) of symptomatic atherosclerotic renal artery stenosis (RAS) still remains a controversial issue, which was reflected by a weak level of evidence in the European Society of Cardiology (ESC) and American

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
25
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(26 citation statements)
references
References 19 publications
0
25
1
Order By: Relevance
“…The issue is clinically important because improvements in BP and RF translate into cardiovascular events risk reduction [4,6,13,14,15]. We found that eGFR increase by at least 11 ml/min/1.73m 2 , as well as systolic and diastolic BP decrease by 20 and 5mmHg or higher following PTA for ARAS, relate to cardiovascular death (CVD) or stroke risk reduction over 5 years [16].…”
Section: Introductionmentioning
confidence: 97%
“…The issue is clinically important because improvements in BP and RF translate into cardiovascular events risk reduction [4,6,13,14,15]. We found that eGFR increase by at least 11 ml/min/1.73m 2 , as well as systolic and diastolic BP decrease by 20 and 5mmHg or higher following PTA for ARAS, relate to cardiovascular death (CVD) or stroke risk reduction over 5 years [16].…”
Section: Introductionmentioning
confidence: 97%
“…The immediate result of PTA is characterised by a high success rate and fairly low periprocedural complication rate [5][6][7]. However, the clinical improvement following PTA of RAS is uncertain [5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…The immediate result of PTA is characterised by a high success rate and fairly low periprocedural complication rate [5][6][7]. However, the clinical improvement following PTA of RAS is uncertain [5][6][7][8]. The effect of PTA is probably a complex issue, as both the effect of PTA on renal function and systolic/diastolic blood pressure (SBP/ DBP), as well as cardiovascular adverse events is at least controversial [6,9,10].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations